Cutaneous manifestations and systemic correlation in patients with lupus erythematosus and its subsets: a study of 40 cases - Mahajan, Rashmi; Ninama, Kishan; Pandya, Ishan; Patel, Rajvee; Bilimoria, F. E. (International Journal of Research in Dermatology, 2018)
Background: The objective was to study various dermatological manifestations and clinical and laboratory features in patients of lupus erythematosus (LE) and its subsets. Methods: This is a cross sectional observational study done in a tertiary care hospital in a rural setup in Piparia, Ta. Waghodiya, Dist. Vadodara, Gujarat. All the patients with clinical features of LE and its subsets were included in the study over a period of 16 months and were subjected to detailed history taking, complete cutaneous and general examination and laboratory investigations. Results: Out of the 40 cases, 22 cases were systemic lupus erythematosus (SLE), 13 cases were discoid lupus erythematosus (DLE), four cases were of Rowell’s syndrome and one case was of mixed connective tissue disorder (MCTD). 97.5% of cases had cutaneous involvement, i.e. photosensitivity (77.5%), oral ulcers, hair loss and malar rash. Systemic symptoms and abnormal laboratory parameters were present in the cases of SLE, Rowell’s syndrome and MCTD, with hematological involvement being the most common in both SLE (77%) and Rowell’s syndrome (100%) and positive anti-nuclear antibody (ANA) titer being the most common abnormal laboratory finding in both SLE (95.4%) and Rowell’s syndrome (100%). The most commonly found antibody was anti-dsDNA (64.3%) in SLE and anti SS-A (100%) in Rowell’s syndrome. Conclusions: Cutaneous features though occasionally subtle, are pointers to a diagnosis of SLE. Hair loss, malar rash and photosensitivity alone or in association with altered hematologic/ANA profile are the key markers of the disease activity.